Theophylline-induced mesenteric periarteritis in F344/N rats - Nyska, Abraham (Arch Toxicol, 1998)
The toxicity and carcinogenic potential of theophylline (an alkaloid bronchodilator drug) was investigated in male and female F344/N rats in 16-day, 14-week, and 2-year gavage and feeding studies. In 16-day studies, rats were fed diets containing 0, 500, 1000, 2000, 4000, and 8000 ppm of theophylline or given 0, 12.5 (twice daily), 25 (once daily), 50 (once daily), 50 (twice daily), 100 (once daily), 200 (once daily), 200 (twice daily), and 400 (once daily) mg theophylline/kg body weight in corn oil by gavage. In 14-week studies, rats were fed diets containing 0, 1000, 2000, and 4000 ppm theophylline or given 0, 37.5, 75, and 150 mg/kg body weight theophylline in corn oil by gavage. In 2-year gavage studies, rats were given 0, 7.5, 25, and 75 mg/kg body weight in corn oil. In 16-day gavage studies, treatment-related periarteritis occurred in arteries of the pancreas and adjacent to the mesenteric lymph nodes of early death male and female rats given 400 mg/kg once daily. In the 14-week studies, treatment-related periarteritis occurred at similar sites and in male rats exposed to 75 and 150 mg/kg, and in all exposed female rats (gavage studies), in females exposed to 1000 ppm, and in both sexes exposed to 2000 and 4000 ppm (feeding studies). In the 2-year study, chronic periarteritis was significantly increased only in the males receiving 75 mg/kg of theophylline. The adventitia, media and intima of medium- and large-sized mesenteric arteries were involved. Similar to other vasodilator chemicals, the pathogenesis of theophylline-induced vascular lesions may be a consequence of hemodynamic changes induced in the vascular wall.